Mass Spectra and Decay Constants of Heavy-Light Mesons: A Case Study of QCD Sum Rules and Quark Model - Halil Mutuk (Advances in High Energy Physics)
We visited mass spectra and decay constants of pseudoscalar and vector heavy-light mesons (B, Bs, D, and DS) in the framework of QCD sum rule and quark model. The harmonic oscillator wave function was used in quark model while a simple interpolating current was used in QCD sum rule calculation. We obtained good results in accordance with the available experimental data and theoretical studies.